2018
DOI: 10.3389/fcell.2018.00019
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers of Age to Enhance Efficacy of Cancer Immunotherapy: The Clout of the Extracellular Matrix

Abstract: There is a growing list of cancer immunotherapeutics approved for use in a population with an increasing number of aged individuals. Cancer immunotherapy (CIT) mediates tumor destruction by activating anti-tumor immune responses that have been silenced through the oncogenic process. However, in an aging individual, immune deregulation is positively correlated with age. In this context, it is vital to examine the age-related changes in the tumor microenvironment (TME) and specifically, those directly affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…Compared to CAR-T targeting CD19 for hematological malignancies, CAR-T targeting GPC3 for hepatocellular carcinoma did not show encouraging e cacy [22]. Various factors affect the therapeutic bene t of CAR-T on HCC, such as a poor tumor tissue microenvironment that limits proliferation and CAR-T cytotoxicity and the dense ECM which limits lymphocyte in ltration into tumor tissue [13,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to CAR-T targeting CD19 for hematological malignancies, CAR-T targeting GPC3 for hepatocellular carcinoma did not show encouraging e cacy [22]. Various factors affect the therapeutic bene t of CAR-T on HCC, such as a poor tumor tissue microenvironment that limits proliferation and CAR-T cytotoxicity and the dense ECM which limits lymphocyte in ltration into tumor tissue [13,25].…”
Section: Discussionmentioning
confidence: 99%
“…Solid tumors have a more complex immunosuppressive microenvironment and there are many immunosuppressive cells and cytokines which inhibit the activation and survival of CAR-T cells within the tumor [11,12]. The dense extracellular matrix (ECM) also prevents CAR-T cells from in ltrating into solid tumors and can affect CAR-T cell activity [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An established tumor contains not only tumor cells but also inflammatory cells, stromal cells, vasculature, and extracellular matrices, which are so called the tumor microenvironment (TME), and immune cells and immunoregulatory cells in the TME form the tumor immune microenvironment . Exploring the characterization of tumor immune microenvironment would be of great value to unravel the mechanism of silenced immune responses in tumor patients . Increasing evidences have confirmed that chemotherapy could influence the expression of immune checkpoints in tumor microenvironment .…”
Section: Introductionmentioning
confidence: 99%
“…8 Exploring the characterization of tumor immune microenvironment would be of great value to unravel the mechanism of silenced immune responses in tumor patients. 9 Increasing evidences have confirmed that chemotherapy could influence the expression of immune checkpoints in tumor microenvironment. 10 It has been reported that PD-1 and/or PD-L1 was upregulated after chemotherapy in leukemia and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%